THE USE OF AUDIO VISUAL MEDIA TO INCREASE THE SECOND YEAR STUDENT LISTENING SKILL (A CLASSROOM ACTION RESEARCH AT MTS. MUHAMMADIYAH TONGKO) - Rusydi, Rusydi; Wahidah, Wahidah; Tandiriterung, Selfi Ravianty (La Ogi : English Language Journal, 2024)
The research aimed to explain, the improvement students’ listening skill in informative listening with vocabulary and memory, then apreciative listening in presentation and perception.To explain the improvement, the research used a Classroom Action Research (CAR) which was conducted in two cycle consist of four meeting. The location of this research was taken at the second grade students of MTs. Muhammadiyah Tongko with the member of the students’ of the object 29 students. The findings of this research were the improvement of the students’ listening skill in term of informative listening and appreciative listening in which the mean score of diagnostic test was 4.09, the mean score of cycle I was 5.57 and the mean score of cycle II was 7.70. The result above indicated that there was a significant improvement of the students’ listening skill in the application of audio visual media with listening answer technique at the second grade students of MTs. Muhammadiyah Tongko.